2020
DOI: 10.5888/pcd17.190307
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Vitamin D on Blood Pressure and Hypertension in the General Population: An Update Meta-Analysis of Cohort Studies and Randomized Controlled Trials

Abstract: What is already known on this topic? The effects of vitamin D on hypertension risk and blood pressure have been explored widely in cohort studies and randomized controlled trials (RCTs), but whether the association is causal still is unknown. What is added by this report? We performed an update meta-analysis of both cohort studies and RCTs in a generally heathy population and found that the dose-response relationship between circulating 25-hydroxyvitamin D level and hypertension risk was approximately L-shaped… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
58
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(81 citation statements)
references
References 54 publications
(35 reference statements)
5
58
1
2
Order By: Relevance
“…However, when examining pooled results of the randomised control trials, vitamin D supplementation was not associated with a significant decrease in the weighted mean differences for either SBP or DBP reduction. 66 Among Eastern James Bay Cree, mean vitamin D concentrations are reported to be lower when compared with data from the Canadian Health Measures Survey. 67 Changes in diet (ie, limited traditional food consumption) and changes to the subsistence way of life influence vitamin D status and bone mineral density levels.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…However, when examining pooled results of the randomised control trials, vitamin D supplementation was not associated with a significant decrease in the weighted mean differences for either SBP or DBP reduction. 66 Among Eastern James Bay Cree, mean vitamin D concentrations are reported to be lower when compared with data from the Canadian Health Measures Survey. 67 Changes in diet (ie, limited traditional food consumption) and changes to the subsistence way of life influence vitamin D status and bone mineral density levels.…”
Section: Discussionmentioning
confidence: 96%
“… 65 Likewise, in a review of CRP and hypertension, antihypertensive medication has been shown to lower circulating CRP levels independently of BP effects, which is possibly why in our study results CRP was found not to be associated with continuous measurement of BP. 11 Additionally, in a meta-analysis of cohort studies and randomised controlled trials examining the effect of vitamin D on BP, Zhang et al 66 report a L-shaped relationship between circulating 25(OH)D levels and hypertension risk; specifically, risk of hypertension was shown to be greater with 25(OH)D levels less than 75 nmol/L. However, when examining pooled results of the randomised control trials, vitamin D supplementation was not associated with a significant decrease in the weighted mean differences for either SBP or DBP reduction.…”
Section: Discussionmentioning
confidence: 99%
“…Apesar de alguns estudos observacionais sugerirem que a deficiência de vitamina D está associada à elevação da pressão ou à maior incidência de hipertensão 445,446 (GR: IIb, NE:A), os estudos com suplementação de vitamina D apresentam resultados inconsistentes [447][448][449] (GR: IIb, NE: A). Portanto, o papel da vitamina D no controle da pressão ainda não está estabelecido.…”
Section: Vitamina Dunclassified
“…Data of these meta-analyses indicate that low vitamin D status is associated with a significantly increased risk of hypertension, cardiovascular events, and cardiovascular mortality. Some of these meta-analyses [ 46 , 47 , 48 , 49 ] not only compared low versus high 25(OH)D categories, but performed a dose–response analysis according to circulating 25(OHD concentrations. Data indicate a nonlinear increase in CVD risk at circulating 25(OH)D concentrations below 50 nmol/L compared with a circulating 25(OH)D concentration around 75 nmol/L, with the highest CVD risk at concentrations below 25 nmol/L.…”
Section: Data On Vitamin D and Cardiovascular Diseases In Humansmentioning
confidence: 99%